Schottky diode like behaviour in Ag/Dy2NiMnO6/FTO device. (2018) - Sariful Sheikh, Md; Chanda, Sadhan; Dutta, Alo; Das, Sayantani; Sinha, T.P.
Abstract: Here, we have discussed the carrier transport phenomena through the interface formed by silver and double perovskite oxide Dy2 NiMnO6 (DNMO). The suitable optical band gap energy and the room temperature conductivity of the synthesized DNMO motivated us to explore the metal/ semiconductor interface. We have used thermionic emission theory to analyze the charge transport mechanism through the metal/semiconductor (i.e. Ag/DNMO) junction. We have studied the effect of temperature on charge carrier transport phenomena and demonstrated the potential applicability of the synthesized DNMO to over crown the research on double perovskite oxide semiconductors.